Prevalence of EGFR Mutations in Patients With Resected Stage I to III Nonsquamous Non–Small Cell Lung Cancer: Results of India Cohort - Ullas Batra; Kumar Prabhash; Vanita Noronha; Ramakant Deshpande; Sachin Khurana; Gull Mohammad Bhat; Rajesh Mistry; Vivek Agarwala; Sajjan Rajpurohit; Bhavesh Poladia; Mansi Sharma; Saquib Zaffar Banday (JCO Global Oncology)
PURPOSEThe spectrum of EGFR is inadequately researched in patients with early-stage non–small cell lung cancer (NSCLC) in India. EARLY-epidermal growth factor receptor (EGFR) India (ClinicalTrials.gov identifier: NCT04742192), as part of a noninterventional, real-world global study, evaluated the prevalence of EGFR mutations in early-stage NSCLC in India.METHODSProspective data from adult patients with surgically resected stage IA to IIIB (American Joint Committee on Cancer eighth edition) NSCLC between March 2021 and October 2022 were analyzed. In addition to descriptive statistics, Fisher's exact test with Monte Carlo was used to determine the association between EGFR mutations and clinicodemographic parameters.RESULTSOf 74 patients (median age, 57.0 [range, 33.0-77.0] years) enrolled from eight centers in India, 73.0% (54 of 74) were males, 56.1% (37 of 66) were nonsmokers, and 95.9% (71 of 74) had adenocarcinoma. The EGFR mutation prevalence was 26.0% (19 of 73), of which Exon-19 deletions were the predominant subtype (13, 68.4%) followed by Exon 21-L858R (4, 21.1%), Exon 20-T790M (1, 5.3%), and compound (1, 5.3%) mutations. Nearly half (48.6%, 36 of 74) of the patients underwent only surgical resection. The remaining 51.4% (38 of 74) of the patients were prescribed neoadjuvant (n = 12; 16.2%) and adjuvant (n = 31; 41.9%) systemic therapies, and one patient (1.4%) received radiotherapy along with systemic therapy. In 60 patients with stage IB to IIIB NSCLC, systemic therapies, mainly platinum-based chemotherapy, were prescribed in 36 (60.0%). Only 8.1% (6 of 74) of the patients were prescribed EGFR-tyrosine kinase inhibitor (TKI), of which two received neoadjuvant and four were planned for adjuvant EGFR-TKI. Two (2.7%) patients were prescribed adjuvant immunotherapy. The univariate analysis showed higher odds of EGFR mutation for females (odds ratio, 3.96; P = .017).CONCLUSIONEARLY-EGFR India results showed the prevalence of EGFR mutation to be 26%. The study emphasized the pressing need for up-front biomarker testing at diagnosis to ensure optimal and timely personalized treatment.